2020
DOI: 10.1038/s41598-020-67852-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal sleep before and during pregnancy with preterm birth and early infant sleep and temperament

Abstract: This study aimed to investigate the association of maternal sleep before and during pregnancy with preterm birth, infant sleep and temperament at 1 month of age. We used the data of the Japan Environment and Children’s Study, a cohort study in Japan, which registered 103,099 pregnancies between 2011 and 2014. Participants were asked about their sleep before and during pregnancy, and the sleep and temperament of their newborns at 1 month of age. Preterm birth data were collected from medical records. Maternal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…We suggest antenatal screening in order to identify potential pregnancy-related symptoms and forms of distress. For example, sleep problems may have serious effects and contribute to adverse pregnancy outcomes or postnatal physical and psychological symptom distress [ 35 , 36 ]. Some symptoms, such as nausea, vomiting, constipation and hemorrhoids, are rarely life-threatening or have adverse consequences but can cause significant distress, not only negatively impacting pregnant women’s quality of life and daily functioning but also leading some women to consider termination of pregnancy or future pregnancy avoidance [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest antenatal screening in order to identify potential pregnancy-related symptoms and forms of distress. For example, sleep problems may have serious effects and contribute to adverse pregnancy outcomes or postnatal physical and psychological symptom distress [ 35 , 36 ]. Some symptoms, such as nausea, vomiting, constipation and hemorrhoids, are rarely life-threatening or have adverse consequences but can cause significant distress, not only negatively impacting pregnant women’s quality of life and daily functioning but also leading some women to consider termination of pregnancy or future pregnancy avoidance [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“… a [ 16 ] and [ 17 ] analyzed the same study population; b [ 21 ] and [ 31 ] studied the same study population; c [ 27 ] and [ 28 ] analyzed the same study population. AIS: Athens Insomnia Scale; BMI: body mass index; ESS: Epworth Sleepiness Scale; PSQI: Pittsburgh Sleep Quality Index.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded cases with missing information about the daytime and nighttime sleep periods of the infant, as this was necessary for analysis. If daytime sleep was longer than nighttime sleep at one month of age, it was assumed that the formation of the sleep–wake rhythm had been delayed 14 . The children who slept more during the day were classified into the “Day sleep” group, while children who slept more during the night or slept equally during the night and day were classified into the “Night sleep” group.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, exposure to environmental factors, such as the light–dark cycle and the mother's lifestyle, may promote or hinder the establishment of the infant's sleep–wake rhythm 12 , 13 . In addition, it has been reported that the mother’s sleeping habits during pregnancy, child’s time of birth, infant’s age in weeks, mother’s history of childbirth, and breastfeeding influence the formation of the sleep–wake rhythm in infants 8 , 14 .…”
Section: Introductionmentioning
confidence: 99%